Essay on the origin of human knowledge - Condillac, Etienne Bonnot De; Aarsleff, Hans (Cambridge university press, 2001)
This work, first published in 1746 and offered here in a new translation, is a highly influential work in the history of philosophy of mind and language, and anticipates Wittgenstein's views on language and its relation to mind and thought.
Includes index.
Keywords: Psychology - Early works to 1850.; Knowledge, Theory of - Early works to 1800.; Language and languages - Philosophy - Early works to 1800.